EFFECT OF FLEXIBILITY TRAINING ON IMPROVING SOME MOTOR ABILITIES AND PERFORMANCE IN HIGH JUMP 12-14 YEARS OLD - Ansam Khazaal Jabbar (Journal Olahraga Rekat (Rekreasi Masyarakat), 2025)
Background. The high jump requires a combination of motor abilities, including flexibility, coordination, and balance, to achieve optimal performance. However, in many young athletes, performance progress is hindered by insufficient attention to motor abilities compared to physical conditioning. This study addresses the problem of suboptimal high jump achievements among athletes aged 12–14 years by examining the role of flexibility training as a targeted intervention. Flexibility training, involving varied exercises designed to improve joint mobility and muscle elasticity, is hypothesized to enhance motor abilities and thereby improve high jump performance. Objectives. The purpose of this study was to investigate the effect of flexibility training on selected motor abilities and high jump achievement in young athletes. Method. An experimental method with a pre-test and post-test design was employed, involving participants aged 12–14 years who underwent an eight-week flexibility training program, three sessions per week, in addition to their regular practice. Measurements included flexibility, coordination, and high jump performance scores before and after the intervention. Results. The results showed a significant improvement in flexibility and coordination, accompanied by a measurable increase in high jump performance. Statistical analysis confirmed that flexibility training contributed positively to the enhancement of motor abilities, which translated into better competition results. Conclusion. In conclusion, flexibility training with varied exercises is an effective and practical approach for developing motor abilities and improving high jump performance in young athletes. This research contributes to training methodology by providing evidence-based support for incorporating structured flexibility programs into youth athletic development plans.